Fertirrigação nitrogenada e potássica na cultura da abobrinha italiana (Cucurbita pepo l.) em ambiente protegido - Costa, André Ribeiro da (2013)
This study aimed to evaluate the growth and production of zucchini plants of hybrid cultivar Novita Plus through the influence of application of nitrogen and potassium by means of irrigation water. The experiment was conducted in greenhouse at the Technical Centre for Irrigation, Department of Agronomy, University of Maringá. The seeds of zucchini Novita Plus cultivar were sown in polystyrene trays with 72 cells and transplant the experimental area occurred 21 days after sowing. The seedlings were planted at a spacing of 1.0 m between rows and 0.7 m between plants. We used micro-irrigation system located drip which was operated at a pressure of 10 m.w.c. Was installed, a dripper per plant, which worked with nominal flow of 4 L h-1. We adopted a completely randomized design in factorial (4 X 4) with three replications. The treatments comprised N rates (0 kg ha-1 de N, 90 kg ha-1 de N, 180 kg ha-1 de N, 270 kg ha-1 de N) and K rates (0 kg ha-1 de K2O, 90 kg ha-1 de K2O, 180 kg ha-1 de K2O, 270 kg ha-1 de K2O) regarding recommended in the literature and plants and were supplied by fertirrigation. Were evaluated the following variables: Number of sheets (NF), number of male flowers (NFM), number of female flowers (NFF), plant height (PH), stem diameter (DCA), average fruit weight (MMF), fruit length (FL), fruit diameter (FD), number of fruits per plant (NFP), index of fixation of fruits (FIF), productivity (PROD), agronomic efficiency of nitrogen fertirrigation (AENF). The following variables were evaluated for growth. Applying the rate of 270 kg ha-1 of N resulted in obtaining zucchini plants with maximum number of leaves (38,5 leaves plant- 1). However, this variable was not affected by potassium application by fertirrigation. The application of doses of 270 kg ha-1 of N and 270 kg ha-1 of K2O gave obtaining plants with the maximum number of male flowers (69,8 male flowers plant- 1 and 53,5 male flowers plant- 1, respectively). Applying the rate 270 kg ha-1 of N and 173,75 kg ha-1 of K2O by fertirrigation promoted of zucchini plants with the maximum number of female flowers (20,17 female flowers plant- 1 and 16,6 female flowers plant- 1, respectively). The application of nitrogen rate of 122,5 kg ha-1 of N and 270 kg ha-1 of K2O gave obtaining zucchini plants with maximum height (44,6 cm and 44 cm, respectively ), while applying the dose of 145 kg ha-1 of N and 270 kg ha-1 of K2O provided the production of plants with the maximum diameter of the stem (0,64 cm and 0,54 cm, respectively). The application of the dose of 136.92 kg ha-1 of N and the dose of 184.17 kg ha-1 of K2O through drip irrigation promoted the production of fruits with the highest average weight (240,17 g fruit-1 and 227,71 grams fruit-1, respectively). The application of doses of 270 kg ha-1 of N and 270 kg ha-1 of K2O fertirrigation promoted by obtaining higher fruit length (19,8 cm and 17,8 cm, respectively). The application of doses of 126,67 kg ha-1 of N and 175 kg ha-1 of K2O provided fruit production with maximum diameter (5,7 cm and 5,16 cm, respectively). The maximum number of fruits per plant (12,1 fruits plant-1 and 7,6 fruits plant-1, respectively) was achieved with the application of 179,17 kg ha-1 of N and 171.25 kg ha-1 of K2O. The highest yield (36,8 t ha-1 and 23.8 t ha-1 ) was obtained with the application of doses of 149,92 kg ha-1 of N and 137,75 kg ha-1 of K2O, respectively. The maximum rate of fruit set (62,7 % and 47,45%, respectively) was achieved with the application by fertirrigation of 138,05 kg ha-1 of N and 233,5 kg ha-1 of K2O. The agronomic efficiency of nitrogen fertirrigation decreased with increasing doses of nitrogen and this decrease was more pronounced at the dose of 270 kg ha-1 of N.